2021
DOI: 10.3389/fnhum.2021.689683
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Parent and Child Perspectives of Living With Cerebral Visual Impairments

Abstract: Cerebral Visual Impairment (CVI) is an umbrella term which includes abnormalities in visual acuity, or contrast sensitivity or colour; ocular motility; visual field and the conscious and unconscious filtering or processing of visual input. Children with CVI have specific needs and problems relating to their development from infancy to adulthood which can impact on their wellbeing. Recent research indicates the complexities of living with CVI but there remains limited information of the full impact of CVI on fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Currently, CVI is not or is minimally part of the mandatory training for most medical professionals, including ophthalmologists, leading to a lack of exposure and confidence in evaluating, diagnosing, and medically treating those with CVI (Harpster et al, 2022). This may be particularly evident for those in whom visual fields and acuity are within typical levels (Goodenough et al, 2021). More intensive training in CVI by professionals in other fields such as optometry, education, occupational therapy, speech-language pathology, orientation and mobility, and more is also needed.…”
Section: With the Above In Mind What Are Some Potential Ways That Pol...mentioning
confidence: 99%
“…Currently, CVI is not or is minimally part of the mandatory training for most medical professionals, including ophthalmologists, leading to a lack of exposure and confidence in evaluating, diagnosing, and medically treating those with CVI (Harpster et al, 2022). This may be particularly evident for those in whom visual fields and acuity are within typical levels (Goodenough et al, 2021). More intensive training in CVI by professionals in other fields such as optometry, education, occupational therapy, speech-language pathology, orientation and mobility, and more is also needed.…”
Section: With the Above In Mind What Are Some Potential Ways That Pol...mentioning
confidence: 99%
“…Parents commonly cite a lack of support, signposting and information at diagnosis as a key barrier to them accessing services to support their children [11,47]. Whilst each individual child will need a bespoke support package, simple adaptations to educational materials (such as enlarged font and/or fewer items per page) and environments (such as reducing clutter and/or considering area of best visual attention) help a lot of children [48].…”
Section: Management Of Children With CVImentioning
confidence: 99%
“…There is often no cure for the features of cerebral visual impairment: rather the impact of visual dysfunction is ameliorated by adopting strategies and modifications to the child’s environment tailored to the child’s unique combination of difficulties [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For children, this encompasses adjustments to enable them to access education and maximise their academic potential. A UK study identified that parental and teacher understanding of the child's CVI and individual information on strategies to support the child were important to promote successful intervention (Goodenough et al, 2021).…”
Section: What Was Known Beforementioning
confidence: 99%